Efek Antioksidan Larutan Kosolven Ekstrak Kulit Buah Manggis (Garcinia mangostana L.) pada Tikus dengan Parameter MDA dan SOD - ROS SUMARNY; LILIEK NURHIDAYATI; SITI SOFIAH; YATI SUMIYATI; FRANSISKA DIANA SANTI (JURNAL ILMU KEFARMASIAN INDONESIA, 2015)
Mangosteen (Garcinia mangostana L.) rinds extract in capsule form has been marketed. a-mangostin, the active compound of G. mangostana had been known has low solubility in water. This study was aimed to measure and compare antioxidant effect of a-mangostin as cosolvent solution to extracts suspentions. 25 rats were divided into 5 groups: negative (I) and positive (II) control, cosolvent solution (III), extract (IV) and extract® (V). Treatment were given for 14 days, free radicals were induced by CCl . MDA were analyzed using thiobarbituric acid method while SOD by using adenochrome assay. Results showed MDA level were: 1.0±0.19; 0.3±0.05; 0.4±0.04; 0.6±0.04 and 0.5±0.00 nmol/mL, whereas SOD activity were: 17±0.0; 123±25.3; 107±19.0; 73±18.9 and 97±27.0 U/mL for group I, II, III, IV and V, respectively. Kruskal Wallis test showed a significant difference in MDA between group III with IV and V (p>0.05), showing cosolvent has higher ability to decrease MDA than the extracts suspension. There were significant differences of SOD between group III and IV (p>0.05), meaning cosolvent has higher ability to increase SOD activity compare to the extracts. Research showed cosolvent has a higher antioxidant effect with potential to inhibit MDA formation by 70% and increase SOD activity by 623%.